Pure Hydrocarbon Materials as Highly Efficient Host for White Phosphorescent Organic Light‐Emitting Diodes: A New Molecular Design Approach. (14th July 2022) - Kong, Fan‐Cheng; Zhang, Yuan‐Lan; Quinton, Cassandre; McIntosh, Nemo; Yang, Sheng‐Yi; Rault‐Berthelot, Joëlle; Lucas, Fabien; Brouillac, Clément; Jeannin, Olivier; Cornil, Jérôme; Jiang, Zuo‐Quan; Liao, Liang‐Sheng; et al.
Abstract: To date, all efficient host materials reported for phosphorescent OLEDs (PhOLEDs) are constructed with heteroatoms, which have a crucial role in the device performance. However, it has been shown in recent years that the heteroatoms not only increase the design complexity but can also be involved in the instability of the PhOLED, which is nowadays the most important obstacle to overcome. Herein, we design pure aromatic hydrocarbon materials (PHC) as very efficient hosts in high‐performance white and blue PhOLEDs. With EQE of 27.7 %, the PHC‐based white PhOLEDs display similar efficiency as the best reported with heteroatom‐based hosts. Incorporated as a host in a blue PhOLED, which are still the weakest links of the technology, a very high EQE of 25.6 % is reached, surpassing, for the first time, the barrier of 25 % for a PHC and FIrpic blue emitter. This performance shows that the PHC strategy represents an effective alternative for the future development of the OLED industry. Abstract : Pure hydrocarbon (PHC) host materials have been designed for blue and white phosphorescent organic light‐emitting diodes (PhOLEDs). The PHC‐based blue PhOLEDs display external quantum efficiency (EQE) higher than 25 %. The PHC‐based white PhOLEDs display an EQE of 27.7 %, which is a similar efficiency to the best reported devices with heteroatom‐based hosts.